William Benbow and the Origin of the General Strike - Carpenter, Niles (Quarterly Journal of Economics, 1921)
William Benbow and the Origin of the General Strike Get access Niles Carpenter Niles Carpenter Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 35, Issue 3, May 1921, Pages 491–499, https://doi.org/10.2307/1884099 Published: 01 May 1921